2009
DOI: 10.1002/jmv.21450
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative human papillomavirus 16 and 18 levels in incident infections and cervical lesion development

Abstract: Human papillomavirus (HPV) RNA levels may be a more sensitive early indicator of predisposition to carcinogenesis than DNA levels. We evaluated whether levels of HPV-16 and HPV-18 DNA and messenger RNA (mRNA) in newly detected infections are associated with cervical lesion development. Female university students were recruited from 1990-2004. Cervical samples for HPV DNA, HPV mRNA, and Papanicolaou testing were collected tri-annually, and women were referred for colposcopically-directed biopsy when indicated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
0
14
1
Order By: Relevance
“…We previously showed that report of more than one new partner in the eight months prior to incident HPV-16 or HPV-18 infection was associated with increased E7 mRNA viral levels (9) (and higher viral levels have been linked with persistent detection (1012)). No statistically significant sexual behavioral determinants of persistent versus transient infections were identified.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that report of more than one new partner in the eight months prior to incident HPV-16 or HPV-18 infection was associated with increased E7 mRNA viral levels (9) (and higher viral levels have been linked with persistent detection (1012)). No statistically significant sexual behavioral determinants of persistent versus transient infections were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it must be remembered that viral replication is not necessary for maintaining the malignant phenotype. In situ assays on cervical cancer cell lines have found that not all HPV copies are transcriptionally active; in women with incident HPV16 infections, HPV E7 mRNA levels, but not viral load, are associated with an increased risk of developing squamous intraepithelial lesions (13,14). Robust measurements of type-specific viral load in samples in which integration status and the expression of viral oncogenes are also defined will continue to provide useful insights into the pathogenesis of HPV-associated disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing levels of HPV viral load seem to be associated with an increased risk of developing cervical pre-cancer (Winer et al, 2009). This is relevant to HPV-associated breast cancer as the viral load in cervical cancer seems to be over 4000 times higher than in breast cancer (Fiander et al, 2007;Khan et al, 2008).…”
mentioning
confidence: 97%